Recognizing the students in order to reinvent the school: From the affirmation of a need to the misleads of a desire | Reconhecer os alunos para reinventar a escola: Da afirmação de uma necessidade aos equívocos de um desejo - Rui Trindade (2009)
In this article, the Portuguese Modern School Movement (MEM) constitutes an object of theoretical reflection, its pertinence deriving from the need to reflect, by means of this movement, upon the goals, the demands and the meaning of educational and curricular mediation projects of all those who explicitly claim their praxological and conceptual separation from the field of instruction pedagogies. With such purpose in mind, we start by identifying the main principles in the field of pedagogies of learning by reading the works of some of the most emblematic pedagogues of the New Education Movement, and we proceed by contrasting them with the MEM pedagogical legacy. As a result, in a first instance, we can expose the current areas of light and shadow crossed by educational, curricular and pedagogical discourses that allegedly belong to the field of pedagogies of learning, and secondly we can reflect upon the adjustments developed within MEM in order to meet the objectives of an educational project characterized by recognizing students as mediators and producers of culture.